Infection Pressure in Men Who Have Sex With Men and Their Suitability to Donate Blood. (25th July 2018) - van Bilsen, Ward P H; Zaaijer, Hans L; Matser, Amy; van den Hurk, Katja; Slot, Ed; Schim van der Loeff, Maarten F; Prins, Maria; van de Laar, Thijs J W
Abstract: Background: Deferral of men who have sex with men (MSM) from blood donation is highly debated. We therefore investigated their suitability to donate blood. Methods: We compared the antibody prevalence of 10 sexually and transfusion-transmissible infections (TTIs) among 583 MSM and 583 age-matched repeat male blood donors. MSM were classified as low risk (lr) or medium-to-high risk (hr) based on self-reported sexual behavior and as qualified or unqualified using Dutch donor deferral criteria. Infection pressure (IP) was defined as the number of antibody-reactive infections, with class A infections (human immunodeficiency virus-1/2, hepatitis B virus, hepatitis C virus, human T-cell lymphotropic virus-1/2, syphilis) given double weight compared to class B infections (cytomegalovirus, herpes simplex virus-1/2, human herpesvirus 8, hepatitis E virus, parvovirus B19). Results: Donors had a lower median IP than qualified lr-MSM and qualified hr-MSM (2 [interquartile range IQR, 1–2] vs 3 [IQR, 2–4]; P < .001). Low IP was found in 76% of donors, 39% of qualified lr-MSM, and 27% of qualified hr-MSM. The prevalence of class A infections did not differ between donors and qualified lr-MSM but was significantly higher in qualified hr-MSM and unqualified MSM. Recently acquired class A infections were detected in hr-MSM only. Compared to blood donors, human herpesviruses were more prevalent in all MSM groups ( P < .001). Conclusions: IP correlates with self-reported risk behavior among MSM. Although lr-MSM might form a low threat for blood safety with regard to class A infections, the high seroprevalence of human herpesviruses in lr-MSM warrants further investigation. Abstract : Allowing men who have sex with men (MSM) with self-reported low-risk sexual behavior to donate blood might not reduce blood safety. However, the higher seroprevalence of human herpesviruses in low-risk MSM compared to donors warrants further investigation.